Is it all worth it? The experiences of new PhDs on the job market, 2007–10 - McFall, Brooke Helppie (J Econ Educ, 2015)
This paper describes the job market experiences of new PhD economists, 2007-10. Using information from PhD programs' job candidate websites and original surveys, the authors present information about job candidates' characteristics, preferences and expectations; how job candidates fared at each stage of the market; and predictors of outcomes at each stage. Some information presented in this paper updates findings of prior studies. However, design features of the data used in this paper may result in more generalizable findings. This paper is unique in comparing pre-market expectations and preferences with post-market outcomes on the new PhD job market. It shows that outcomes tend to align with pre-market preferences, and candidates' expectations are somewhat predictive of their outcomes. Several analyses also shed light on sub-group differences.